Математичне та програмне забезпечення оптимального розподілу інформаційних ресурсів серед вузлів обчислювальних мереж - Тичковський, Р. О.; Цегелик, Г. Г. (Eastern-European Journal of Enterprise Technologies, 2020)
The approach to the building of mathematical models for optimal copies of file allocation and performance of computers amongst nodes of computing networks is described. The heuristic and genetic algorithm for realization of the received mathematical models is proposed